2016
DOI: 10.3390/ijms17071169
|View full text |Cite
|
Sign up to set email alerts
|

Immune Checkpoint Inhibitors: A New Opportunity in the Treatment of Ovarian Cancer?

Abstract: Epithelial ovarian cancer (EOC) is the leading cause of death for gynecological cancer. The standard treatment for advanced stage is the combination of optimal debulking surgery and platinum-based chemotherapy. Nevertheless, recurrence is frequent (around 70%) and prognosis is globally poor. New therapeutic agents are needed to improve survival. Since EOC is strongly immunogenic, immune checkpoint inhibitors are under evaluation for their capacity to contrast the “turn off” signals expressed by the tumor to es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
53
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(54 citation statements)
references
References 81 publications
0
53
0
1
Order By: Relevance
“…There has been dramatic success in the treatment of various advanced solid tumor types such as melanoma, renal cancer, lung cancer, head and neck cancer with the novel class of immunomodulatory anticancer agents called immune checkpoint inhibitors (98)(99)(100)(101)(119)(120)(121). These therapeutics are able to block inhibitory molecules and their receptors on effector immune cells, which leads to a robust T-cell response against the tumor.…”
Section: The Role Of Immune Checkpoint Inhibitors In Glioblastoma Immmentioning
confidence: 99%
See 1 more Smart Citation
“…There has been dramatic success in the treatment of various advanced solid tumor types such as melanoma, renal cancer, lung cancer, head and neck cancer with the novel class of immunomodulatory anticancer agents called immune checkpoint inhibitors (98)(99)(100)(101)(119)(120)(121). These therapeutics are able to block inhibitory molecules and their receptors on effector immune cells, which leads to a robust T-cell response against the tumor.…”
Section: The Role Of Immune Checkpoint Inhibitors In Glioblastoma Immmentioning
confidence: 99%
“…Immune checkpoint inhibitors represent a significant breakthrough in the treatment of various advanced tumor types (such as melanoma, renal cancer, lung cancer, head and neck cancer, and urinary bladder cancer) in recent years that has dramatically changed the prognosis of patients with cancer (98)(99)(100)(101)(119)(120)(121). In some cases, therapy with these drugs means long-term disease control or hopefully even cure.…”
Section: The Role Of Immune Checkpoint Inhibitors In Glioblastoma Immmentioning
confidence: 99%
“…Moreover, BRCA1-2 mutated tumors showed a significantly increased CD3 + and CD8 + TIL number anda significantly higher expression of PD-1 and PD-L1 compared with HR-proficient tumors. Therefore, BRCA1-2-mutated HGSOCs could represent a subset of tumors fit for treatment with immune checkpoint inhibitors alone or in combination with poly(adenosine diphosphate (ATP-ribose) polymerases (PARP) inhibitors (57)(58)(59). Moreover, Strickland et al (60) found that 3 out of 30 (10%) CCOCs exhibited microsatellite instability (MSI) and that CCOCs with MSI had a higher number of CD3 + TILs and higher number of PD1-positive TILs compared with both microsatellite stable (MSS) CCOCs Gadducci and Guerrieri: Immune Checkpoint Inhibitors in Gynecological Cancers (Review) 5957 The NCT02571725 trial will assess the side-effects and best dose of tremelimumab when given together with the PARP inhibitor olaparibin patients with recurrent platinumsensitive or platinum-resistant EOC, fallopian tube cancer (FTC) or primary peritoneal cancer (PPC) and germline BRCA1 or BRCA2 mutation.…”
Section: Epithelial Ovarian Cancermentioning
confidence: 99%
“…The latter one having had already been adopted a jester role against the immune system [27]. Several antagonists of PD-1 and PD-L1 have been tested in ovarian cancer.…”
Section: Ovarian Cancermentioning
confidence: 99%